Activation of IGF-1 pathway and suppression of atrophy related genes are involved in Epimedium extract (icariin) promoted C2C12 myotube hypertrophy - Yi-An Lin (Nature Portfolio, 2021)
Abstract The regenerative effect of Epimedium and its major bioactive flavonoid icariin (ICA) have been documented in traditional medicine, but their effect on sarcopenia has not been evaluated. The aim of this study was to investigate the effects of Epimedium extract (EE) on skeletal muscle as represented by differentiated C2C12 cells. Here we demonstrated that EE and ICA stimulated C2C12 myotube hypertrophy by activating several, including IGF-1 signal pathways. C2C12 myotube hypertrophy was demonstrated by enlarged myotube and increased myosin heavy chains (MyHCs). In similar to IGF-1, EE/ICA activated key components of the IGF-1 signal pathway, including IGF-1 receptor. Pre-treatment with IGF-1 signal pathway specific inhibitors such as picropodophyllin, LY294002, and rapamycin attenuated EE induced myotube hypertrophy and MyHC isoform overexpression. In a different way, EE induced MHyC-S overexpression can be blocked by AMPK, but not by mTOR inhibitor. On the level of transcription, EE suppressed myostatin and MRF4 expression, but did not suppress atrogenes MAFbx and MuRF1 like IGF-1 did. Differential regulation of MyHC isoform and atrogenes is probably due to inequivalent AKT and AMPK phosphorylation induced by EE and IGF-1. These findings suggest that EE/ICA stimulates pathways partially overlapping with IGF-1 signaling pathway to promote myotube hypertrophy.